Algae Extraction Controllable Delamination of Vanadium Carbide Nanosheets with Enhanced Near‐Infrared Photothermal Performance. (27th February 2020) - Zada, Shah; Dai, Wenhao; Kai, Zhang; Lu, Huiting; Meng, Xiangdan; Zhang, Yiyi; Cheng, Yaru; Yan, Fang; Fu, Pengcheng; Zhang, Xueji; Dong, Haifeng
Abstract: The two‐dimensional (2D) vanadium carbide (V2 C) MXene has shown great potential as a photothermal agent (PTA) for photothermal therapy (PTT). However, the use of V2 C in PTT is limited by the harsh synthesis condition and low photothermal conversion efficiency (PTCE). Herein, we report a completely different green delamination method using algae extraction to intercalate and delaminate V2 AlC to produce mass V2 C nanosheets (NSs) with a high yield (90 %). The resulting V2 C NSs demonstrated good structural integrity and remarkably high absorption in near infrared (NIR) region with a PTCE as high as 48 %. Systemic in vitro and in vivo studies demonstrate that the V2 C NSs can serve as efficient PTA for photoacoustic (PA) and magnetic resonance imaging (MRI)‐guided PTT of cancer. This work provides a cost‐effective, environment‐friendly, and high‐yielding disassembly approach of MAX, opening a new avenue to develop MXenes with desirable properties for a myriad of applications. Abstract : V2 C‐Nanoblätter (NSs) wurden durch eine nachhaltige Methode synthetisiert, bei der V2 AlC‐Kristalle durch Algenextraktion in wässriger Lösung geätzt werden. Die resultierenden V2 C‐NSs zeigten eine gute strukturelle Integrität und eine hohe Absorption im Nahinfrarotbereich (NIR) mit guter photothermischer Umwandlungseffizienz (PTCE). Die V2 C‐NSs ergaben eine hochwirksame photothermische In‐vitro‐ und In‐vivo‐Ablation von Tumoren.